PROSPECTS FOR DEVELOPMENT OF GETTING THE COAL IN SIBERIA - Kurlenya M.V.; Cheskidov V.I. (My University, 2001)
Generation of electric energy at various power stations including those operating on pulverized coal has been considered. It has been shown that generation of electric energy with the use of the pulverized coal is the most efficient method. In connection with this, the main trends in development of getting the coal in Eastern regions of Russia are discussed. Particular attention is paid to advisability of increase in coal getting by meant of opencast method. Prospects for Kuznetskij and Kansk-Achinsk coal fields are discussed. It has been shown that improvement in quality of coal products is one of the main trends in enhancement of competitiveness of coal industry.